2019
DOI: 10.1039/c8tb02635a
|View full text |Cite
|
Sign up to set email alerts
|

Development of a red-light emission hypoxia-sensitive two-photon fluorescent probe for in vivo nitroreductase imaging

Abstract: A red-light emission nitroreductase-activatable two-photon fluorescent probe, namely NRP, was developed for monitoring of degree of hypoxia in cells and in vivo nitroreductase imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…Prior to cell imaging experiments, the cytotoxicities of the nanoprobe NP-SPT-NO 2 against 4T1 cell line (murine mammary carcinomac ell line overexpressing NTR under hypoxia [30] )a nd LO2 cell line (normal human hepatic cell line which has no overexpression of NTR) were evaluated ( Figure S24), and the result confirmed that the nanoprobe presents little cytotoxicity. The intracellular imaging of NTR by NP-SPT-NO 2 was investigated in 4T1 cells by fluorescencei maging.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Prior to cell imaging experiments, the cytotoxicities of the nanoprobe NP-SPT-NO 2 against 4T1 cell line (murine mammary carcinomac ell line overexpressing NTR under hypoxia [30] )a nd LO2 cell line (normal human hepatic cell line which has no overexpression of NTR) were evaluated ( Figure S24), and the result confirmed that the nanoprobe presents little cytotoxicity. The intracellular imaging of NTR by NP-SPT-NO 2 was investigated in 4T1 cells by fluorescencei maging.…”
Section: Resultsmentioning
confidence: 80%
“…In addition, optoacoustic (OA) imaging for NTR in 4T1 cells by the nanoprobe are shown in Figure S26. Clearly, after incubation with NP-SPT-NO 2 under hypoxia, strong OA signals as ar esult of irradiation at 690 nm could be observed in 4T1 cancerc ells, [30] whereas the OA signals (irradiated at 690 nm) were insignificant in the cells under normoxia. These results indicate that the NP-SPT-NO 2 can respond to thei ntracellular NTR, thereby producings trong fluorescent and optoacousticsignals.…”
Section: Resultsmentioning
confidence: 92%
“…As displayed in Figure S27, NP‐Q‐NO 2 shows low cytotoxicity against 4T1 cells. Afterwards, the nanoprobe was employed to image endogenous nitroreductase in 4T1 cells (the murine mammary carcinoma cell line, which is known to overexpress nitroreductase under hypoxia) . From Figure S28, one can see that the cells incubated with the nanoprobe under hypoxic conditions for 0.5 h exhibited evident fluorescence, either under the excitation of 675 nm LED light or 808 nm laser light (at 50 mW cm −2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nitroreductase (NTR) is an endogenous enzyme that overexpressed in hypoxic tumors, and the concentration of NTR is directly concerned to the degree of hypoxia. [10] NTR is seen as an indicator of highly invasive diseases in various hypoxic tumors and NTR overexpression plays important roles in tumor invasion, progression and angiogenesis [11]. Further studies show that the hypoxic status of solid tumors is closely related to the process of tumor progression [12].…”
Section: Introductionmentioning
confidence: 99%